Refleksi Makna Kehidupan Dalam film Nanti Kita Cerita Tentang Hari Ini karya Marchella dan Lagu Rehat Kunto Aji - Hasnah Azmi Aulia (JOURNAL SAINS STUDENT RESEARCH, 2026)
The purpose of this study is to determine the form of the song rehat, to find out the meaning contained in the song rehat to find out the relationship of the song rehat with the film scene we will tell about today. The data analysis method used is a qualitative descriptive method with a Roland Barthes semiotic approach. The data sources of this study, namely the novel written by Marchella FP in 2018 and the film NKCTHI produced by Vinema Pictures and the lyrics of Kunto Aji's song obtained from the internet and audio. This writing was analyzed using reading techniques and note-taking techniques. The author read and watched the film NKCTHI and the lyrics of the song rehat, then noted the elements contained in the novel. The results of this study found 1) Reflection of the meaning of life from the film NKCTHI and the song Rehat; 2) The meaning of the meaning of denotation, connotation and myth from the film NKCTHI and the lyrics of the song Rehat.